Character Education in Islamic Education: Strengthening and Implementing in the Digital Age - Rahayu, Windi; Zukri, Alda; Maimunah, Arbain; Mayang Sari, Dinda; Jannah, Raudatul; Ikhlas, Muhammad (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2023)
The digital era is marked by massive technological developments, having a significant impact on the world of education. The study aims to delineate the application and strengthening of character education through Islamic Religious Education in addressing the negative impact of technology in the digital era. The research method uses a library study as an approach to analyzing the concept of the application and strengthening of character education through Islamic religious education. The results of the study include various findings that address these concepts, highlighting strategies and methods that can be used to enhance the character of students. The research results show that Islamic-based character education is crucial in view of the impact of technological changes that affect interaction, communication, and behavior. Ethical guidance in the use of technology can be obtained through Islamic religious education, with emphasis on the application of everyday character through cultivation and uniformity. Successful character education requires shared responsibility from schools, communities, and parents. The recommendation of this study is the need for further integration between technology and character education through Islamic Religious Education. It requires a joint effort from education, parents, and the community to ensure that the use of technology is done positively, in line with student character formation.